Silver incorporated partially reduced NiCo-layered double hydroxide frameworks for asymmetric supercapacitors. (October 2020) - Li, Xiaoyu; Khalafallah, Diab; Wu, Zongxiao; Zhi, Mingjia; Hong, Zhanglian
Highlights: Silver incorporated partial reduced Nickel-Cobalt layered double hydroxide have been synthesized using a simple treatment with NaBH4 solution at room temperature. High specific capacitance and excellent rate capability have been achieved. High energy, high power density and excellent cycle stability can be obtained in the aqueous asymmetry capacitor. Abstract: Asymmetric supercapacitors have emerged as one of the most appropriate energy storage systems. Enhancing the specific capacity of electrode materials at high current densities is a critical issue in asymmetric capacitors. Herein, we optimized a simple strategy to develop partial reduced hierarchical nanosheets shaped nickel-cobalt layered double hydroxide with Ag nanoparticles for efficient charge storage. The composite cathodes are prepared using a mild hydrothermal method followed by a liquid phase reduction process. Benefiting from the electric conductivity tuning, the hybrids reveal better capacitive performances. Among all, the nickel-cobalt layered double hydroxide with 5 wt.% Ag decoration presents a high specific capacitance of 1338 F g − 1 at a current density of 10 A g − 1 with a good capacity retention of 660 F g − 1 at 60 A g − 1, implying its fascinating rate capability. Besides, the established capacitor device achieves an energy density of 43.07 Wh kg −1 at a power density of 400 W kg −1 . Interestingly, the device exhibits excellent long-term durability for 10, 000 consecutive cycles of repeated charge-discharge processes at 12.5 A g − 1 with a capacity retention of 89.6%. Such a high performance suggests a practical and feasible approach as three-dimensional (3D) electrode tailoring for sustainable energy storage devices.